Effect of boron deficiency on the photosynthetic performance of sugar beet cultivars with contrasting boron efficiencies - Song, Xin; Song, Baiquan; Huo, Jialu; Liu, Huajun; Adil, Muhammad Faheem; Jia, Qiue; Wu, Wenyu; Kuerban, Abudukadier; Wang, Yan; Huang, Wengong (Frontiers in Plant Science, 2023)
Boron (B) deficiency severely affects the quality of sugar beet production, and the employment of nutrient-efficient varieties for cultivation is a crucial way to solve environmental and resource-based problems. However, the aspect of leaf photosynthetic performance among B-efficient sugar beet cultivars remains uncertain. The objective of the present study was to determine the impacts of B deficiency on leaf phenotype, photosynthetic capacity, chloroplast structure, and photochemical efficiency of the contrasting B-efficiency sugar beet cultivars. The results indicated that the growth of sugar beet leaves were dramatically restricted, the net photosynthetic rate was significantly decreased, and the energy flux, quantum yield, and flux ratio of PSII reaction centers were adversely affected under B deficiency. Compared to the KWS0143 cultivar, the average leaf area ratio of the KWS1197 cultivar experienced less impact, and its leaf mass ratio (LMR) increased by 26.82% under B deficiency, whereas for the KWS0143 cultivar, the increase was only 2.50%. Meanwhile, the light energy capture and utilization capacity of PSII reaction centers and the proportion of absorbed light energy used for electron transfer were higher by 3.42% under B deficiency; KWS1197 cultivar managed to alleviate the photo-oxidative damage, which results from excessive absorbed energy (ABS/RC), by increasing the dissipated energy (DIo/RC). Therefore, in response to B deprivation, the KWS1197 cultivar demonstrated greater adaptability in terms of morphological indices and photosynthetic functions, which not only explains the improved performance but also renders the measured parameters as the key features for varietal selection, providing a theoretical basis for the utilization of efficient sugar beet cultivars in future.